Abnormalities in Glutamate Metabolism and Excitotoxicity in the Retinal Diseases - Makoto Ishikawa (Scientifica)
In the physiological condition, glutamate acts as an excitatory neurotransmitter in the retina. However, excessive glutamate can be toxic to retinal neurons by overstimulation of the glutamate receptors. Glutamate excess is primarily attributed to perturbation in the homeostasis of the glutamate metabolism. Major pathway of glutamate metabolism consists of glutamate uptake by glutamate transporters followed by enzymatic conversion of glutamate to nontoxic glutamine by glutamine synthetase. Glutamate metabolism requires energy supply, and the energy loss inhibits the functions of both glutamate transporters and glutamine synthetase. In this review, we describe the present knowledge concerning the retinal glutamate metabolism under the physiological and pathological conditions.